Determination of the beam position in laser deep penetration welding using coaxially acquired images of the keyhole front and machine learning - Dilger, Pablo; Forster, Carola; Klein, Elias; Burger, Silvana; Eschner, Eric; Schmidt, Michael (Proceedings of the Lasers in Manufacturing (LiM) 2021, 2021)
The joining technology of laser beam welding offers high flexibility and productivity. However, the small laser beam focus demands dependable quality assurance to ensure a sufficient connection of the parts. In keyhole welding of metal sheets in butt joint configuration, a gap is visible at the keyhole front, which correlates with the leading joint position. This process feature can be used for quality control by arranging a high-speed camera coaxially to the laser beam to monitor the keyhole. Here, we present a machine learning approach for a robust determination of the beam position relative to the joint based on the keyhole front morphology. For this purpose, we conducted a series of experiments to produce a set of labeled images, which are used to train a convolutional neural network. After training on the data, the network can predict the position of the keyhole front gap, setting the foundation for a quality control syste
Keywords: laser deep penetration welding; machine learning; image processing; quality assurance

Observation of the melt dynamics during laser remote fusion cutting - Burger, Silvana; Dilger, Pablo; Schwarzkopf, Karen; Staudt, Tobias; Schmidt, Michael (Procedia CIRP, 2022)
Laser remote fusion cutting (RFC) offers a method for laser fusion cutting of metal sheets without need for a cutting gas. It is closely related to laser keyhole welding, which can transition into RFC for suitable parameters, such that the pressures in the process zone lead to a melt ejection on the bottom of the metal sheet. The mechanisms leading up to the melt expulsion are not fully understood yet and need further investigation. In this work, the cutting front is observed through a borosilicate glass sheet using a high-speed imaging system. In the setup, the glass sheet and a sample metal sheet are clamped together and the process zone is set directly at the interface between metal and glass. This setup allows for the observation of the melt dynamics adjacent to the glass sheet. In the experiments, the keyhole formation and the cutting front are investigated using a 6 kW disk laser and different feed velocities for cutting.<br

Quantification of Melt Dynamics from High-Speed Observations Within the Remote Fusion Cutting Regime by Means of Image Processing - Burger, Silvana; Dilger, Pablo; Eschner, Eric; Schmidt, Michael (2021)
Keywords: Laser cutting; Remote fusion cutting; Image processing

Revealing the influence of ring-shaped beam profiles in high-speed laser beam microwelding by synchrotron x-ray imaging - Schwarzkopf, Karen; Burger, Silvana; Chechik, Lova; Forster, Carola; Döring, Markus; Spurk, Christoph; Hummel, Marc; Olowinsky, Alexander; Beckmann, Felix; Moosmann, Julian; Schmidt, Michael (Journal of Laser Applications, 2024)
Laser beam microwelding is a precise technique for joining miniature metal components with high feed rates, which is crucial for productivity. However, high feed rates provoke humping formation—periodic beadlike protuberances along the weld seam—that compromise weld integrity. While humping has been associated with the keyhole transition from a narrow to an elongated shape using standard laser intensity distributions (e.g., Gaussian, top-hat), the impact of complex beam profiles, like ring-shaped intensity distributions, remains less understood. In this work, the influence of core-only, ring-only, and superimposed core-ring intensity distributions on humping formation during laser beam microwelding is investigated by means of synchrotron x-ray imaging. Single-track experiments on stainless steel (1.4404) at 1000 mm/s reveal that the keyhole geometry shifts from deep and narrow with core-only power input to shallow and elongated with ring-only power input. Using a superimposed core-ring intensity distribution (Pc = 300 W, Pr = 600 W) results in a U-shaped capillary and the reduction of the humping amplitude by nearly 80% (from 45.61 μm with core-only to 10.29 μm). The additional laser power comes with the tripling of the melt pool width (from 81 μm with core-only to 263 μm) likely decreasing the melt flow velocity. The reduced variability of the capillary length present for the superimposed intensity distribution further indicates a stabilized evaporation behavior. This work provides valuable insights into mitigating humping formation during laser beam microwelding of stainless steel at elevated feed rates using core-ring intensity distributions.<br

Shedding Light on Gas-Dynamic Effects in Laser Beam Fusion Cutting: The Potential of Background-Oriented Schlieren Imaging (BOS) - Burger, Silvana; Schwarzkopf, Karen; Klämpfl, Florian; Schmidt, Michael (Sensors, 2023)
In laser beam fusion cutting of metals, the interaction of the gas jet with the melt determines the dynamics of the melt extrusion and the quality of the resulting cutting kerf. The gas-dynamic phenomena occurring during laser beam cutting are not fully known, especially regarding temporal fluctuations in the gas jet. The observation of gas and melt dynamics is difficult because the gas flow is not directly visible in video recordings and access to the process zone for observation is limited. In this study, the problem of imaging the gas jet from the cutting nozzle is addressed in a novel way by utilizing the striation pattern formed at the cutting kerf as a background pattern for background-oriented Schlieren imaging (BOS). In this first feasibility study, jets of different gas nozzles were observed in front of a solidified cutting kerf, which served as a background pattern for imaging. The results show that imaging of the characteristic shock diamonds of cutting nozzles is possible. Furthermore, the resulting shock fronts from an interaction of the gas jet with a model of a cutting front can be observed. The possibility of high-speed BOS with the proposed method is shown, which could be suitable to extend the knowledge of gas-dynamic phenomena in laser beam fusion cutting.<br
Keywords: laser beam fusion cutting; laser material processing; process observation; high-speed imaging; Schlieren imaging; background-oriented schlieren (BOS); gas dynamics; gas jets; shock diamonds

Weld Classification with Feature Extraction by FRESH Algorithm based on Surface Topographical Optical Coherence Tomography Data for Laser Welding of Copper - Will, Thomas; Kohl, Jannis; Burger, Silvana; Holbling, Claudio; Müller, Lars; Schmidt, Michael (IEEE Access, 2022)
The topographical information of a weld seam bears information about quality relevant characteristics such as humping or spatter. Optical coherence tomography (OCT) can be used for inline scanning the weld topography coaxially mounted at a laser scanning optic. Feature extraction from this topographical information is challenging due to finding mathematical representations for the identification of relevant features. Feature extraction based on scalable hypothesis tests (FRESH) allows for feature extraction by a combination of various time series characterization methods. FRESHs feature selection is supported with an automatically configured hypothesis test and hence allows for quick extraction of significant features from sensing data in laser welding processes. In this work, a proof-of-concept is demonstrated for weld result categorization from OCT data by feature extraction using the FRESH algorithm. Changes in weld topography are characterized in a vast variety of process parameters for weld categories such as spatter, deep penetration welding, humping and heat conduction welding. As a result, a quantified separation of weld categories is possible and shows the feasibility of the FRESH algorithm for future quality assessments with different sensing technologies in laser welding.
CRIS-Team Scopus Importer:2022-10-21
Keywords: classification; copper; Feature extraction; FRESH; Heating systems; interferometry; laser welding; machine learning; Measurement by laser beam; OCT; optical coherence tomography; Optical imaging; Optical interferometry; process control; process monitoring; surface topography; Surface topography; Welding